STUDY OF MITOTIC INDEX PERCENTAGE BY THE INFLUENCE OF DIFFERENT CONCENTRATIONS OF MUTAGENSIS (COLCHICINE) IN DIFFERENT TIME DURATION ON TWO VARIETIES OF CREPIS CAPILLARIES VIA TISSUE CULTURE TECHNIQUE - M. S. DUHOKY , MOSLEH; ZIBARI, PAYMAN. A. A. (Journal of Duhok University, 2020)
Theseexperiments were conducted at Plant Tissue Culture Laboratory/ college of Agricultural Engineering science / University of Duhok during the period from January 2011 to May 2013. The objectives of this study were to study the effects of different concentrations colchicine on mitotic index of Crepis capillaris (without and with 2B chromosomes) through long term callus culture until regeneration of plants from the callus, to investigate the effectivity of different concentrations of these chemicals in mitotic index induction in long-term callus culture. In general high concentration of colchicine and Crepis capillaries with 2B chromosomehave significant increase in mitotic index level as compared with other treatments however there were no significant differences between the two time durations in all passages except at passage five which performed that the first time duration of shaking recorded higher rate of callus cell mitotic index